INVESTING IN HUMAN CAPITAL IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT AND GLOBAL AI TRANSFORMATION - Nalyvaiko, Nataliia (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
The paper explore the features of investing in human capital in the context of global transformations caused by digitalization, environmental challenges, and the development of artificial intelligence. The growing role of “green human capital” as a key factor in ensuring sustainable economic development is substantiated. The impact of investments in education, healthcare, and the development of competencies on labor productivity and economic growth is revealed. The transformation of the labor market under the influence of digital technologies and AI is analyzed, and the significance of the concept of lifelong education is determined. Attention is focused on the need to form modern approaches to stimulating the development of human capital in Ukraine.